BIBLIOGRAFI TUNKU ABDUL RAHMAN PUTRA AL-HAJ - Suriyana binti Mohd. Noor; Hidayati binti Haron; Hidayati binti Haron (Yayasan Kepimpinan Perdana, 2013)
Bibliography of Tunku Abdul Rahman Putra al-Haj, the first prime minister of Malaysia